Decision Support System of Student Education Assistance Using Analytical Hierarchy Process (AHP) Sunan Giri Foundation - Asromah Al Alawiyah; Haris Yuana; Wahyu Dwi Puspitasari (Procedia of Engineering and Life Science, 2021)
Student education assistance is a Foundation program for students to gain access to decent education services, prevent dropping out of school, attract poor students to return to school. In its application, there are problems in determining, one of which is the inaccuracy of the recipient's target. This is due to the many tasks, obligations and work programs that must be completed on time by division. Therefore, the solution that can be done for time efficiency in helping the foundation is to create a system using the Analytical Hierarchy Process (AHP). Because the decision support system is able to solve management problems in producing the best alternative to support decisions taken by decision makers. The criteria used in this system are student status, average value of report cards, SKMT (Certificate of Disability), parental income, parental dependents, home ownership status and achievement. The results of the tests carried out using the black box testing method obtained an accuracy value of 70.58%, meaning that the application has run in accordance with the expected results, while the accuracy of the beta testing of the questionnaire results to the validator is 86% and the testing to prospective users is 87.81%.